العلاقات الجزائرية المغربية في عهد بن بلة وبومدين 1962 - 1978 - بوقصة مريم; د/ كعبوش بومدين (جامعة عمار ثليجي الاغواط, 2023)
ملخص : تناولنا في مشروعنا هذا موضوع تحت عنوان العلاقات الجزائرية المغربية في عهد الرئيس أحمد بن بلة وعهد الرئيس هواري بومدين من فترة 1962-1978 ، حيث تناولنا في البداية قترة حكم بن بلة وبومدين ومميزاتها ثم انتقلنا إلى العلاقات الودية والتعاونية بين الجزائر والمغرب حيث تطرقنا إلى العلاقات الجزائرية المغربية أثناء الثورة التحريرية . كما تضمنت التحالف من أجل الوحدة والكفاح المشترك ، ثم إنتقلنا إلى العلاقات العدائية بين الجزائر والمغرب بعدها تطرفنا إلى أسباب النزاع الحدودي بين الجزائر والمغرب ، ثم المواجهة العسكرية وبعدها قضية الصحراء الغربية والنزاع حولها . summary : In our project, we dealt with a topic under the title of Algerian-Moroccan relations during the era of President Ahmed Ben Bella and the era of President Houari Boumediene from the period 1962-1978, where we initially dealt with the period of rule of Ben Bella and Boumediene and its characteristics, then we moved to the friendly and cooperative relations between Algeria and Morocco, where we touched on Algerian relations. Morocco during the liberation revolution. It also included the alliance for unity and joint struggle, then we moved to the hostile relations between Algeria and Morocco, after which we turned to the causes of the border dispute between Algeria and Morocco, then the military confrontation, and then the issue of Western Sahara and the dispute over it